(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The wild edible vegetables are been traditionally accepted by local populations for their nutritional value, taste and odour. A priliminary study was undertaken during September 2022 in Karjat Tehsil to survey the popular wild edible vegetables, their properties, importance in diet and use. A total of Eight species were studied and reported from the area during the study. Key words: Wild edible vegetables, nutritionally rich, Karjat.